Population Structure, Genetic Variation, and Linkage Disequilibrium in Perennial Ryegrass Populations Divergently Selected for Freezing Tolerance - Kovi, Mallikarjuna Rao; Fjellheim, Siri; Sandve, Simen R.; Larsen, Arild; Rudi, Heidi; Asp, Torben; Kent, Matthew Peter; Rognli, Odd Arne (Frontiers in Plant Science, 2015)
Low temperature is one of the abiotic stresses seriously affecting the growth of perennial ryegrass (Lolium perenne L.), and freezing tolerance is a complex trait of major agronomical importance in northern and central Europe. Understanding the genetic control of freezing tolerance would aid in the development of cultivars of perennial ryegrass with improved adaptation to frost. The plant material investigated in this study was an experimental synthetic population derived from pair-crosses among five European perennial ryegrass genotypes, representing adaptations to a range of climatic conditions across Europe. A total number of 80 individuals (24 of High frost [HF]; 29 of Low frost [LF], and 27 of Unselected [US]) from the second generation of the two divergently selected populations and an unselected (US) control population were genotyped using 278 genome-wide SNPs derived from perennial ryegrass transcriptome sequences. Our studies investigated the genetic diversity among the three experimental populations by analysis of molecular variance and population structure, and determined that the HF and LF populations are very divergent after selection for freezing tolerance, whereas the HF and US populations are more similar. Linkage disequilibrium (LD) decay varied across the seven chromosomes and the conspicuous pattern of LD between the HF and LF population confirmed their divergence in freezing tolerance. Furthermore, two Fst outlier methods; finite island model (fdist) by LOSITAN and hierarchical structure model using ARLEQUIN, both detected six loci under directional selection. These outlier loci are most probably linked to genes involved in freezing tolerance, cold adaptation, and abiotic stress. These six candidate loci under directional selection for freezing tolerance might be potential marker resources for breeding perennial ryegrass cultivars with improved freezing tolerance.